Optimization of tail beam configurations in pressure vessel skirts for enhanced structural integrity - Satya Prakash M; Thenarasu M; Mohanraj T; Venkata Roshan M (Results in Engineering, 2025)
Pressure vessels are critical components across various industries, designed to safely contain fluids under extreme pressure. Ensuring their structural integrity, particularly in challenging environments, is essential for both operational efficiency and safety. A major vulnerability in pressure vessels is the skirt section, which bears the entire vessel weight and is prone to failure due to excessive stresses and deformation. This study aims to enhance the design of pressure vessel tail beams, focusing on configurations that minimize stress concentrations and prevent skirt failures during erection. A dual-method approach was adopted, combining Design by Rule (DBR) and Design by Analysis (DBA) techniques in accordance with ASME standards. Advanced computational modeling and finite element analysis (FEA) were carried out using ANSYS software to investigate multiple tail beam configurations, including a novel Plus-shaped arrangement. Findings indicate that the Plus-shaped configuration reduces skirt stress by approximately 78% compared to standard single-beam designs, offering superior structural support and durability. The integration of DBR and DBA enhances design validation, ensuring compliance with safety criteria while optimizing material efficiency. These results provide actionable insights for improving pressure vessel reliability and establishing best practices in structural engineering for high-stress environments.